O imaginário religioso de pacientes de hanseníase: um estudo comparativo entre ex-internos dos asilos de São Paulo e atuais portadores de hanseníase The religious imaginary of Hansen's disease patients: a comparative study of former inmates of the asylums of São Paulo and current Hansen's disease patients - André Gonçalves Mellagi; Yara Nogueira Monteiro (História, Ciências, Saúde: Manguinhos)
Analisa a religiosidade de pacientes portadores de hanseníase que viveram dois períodos distintos da história do tratamento dos doentes: o do internamento em asilos e o da prática atual. Dez entrevistas semiestruturadas focalizaram saúde, religião e hanseníase, abordando os meios de enfrentamento religioso nos dois grupos. No grupo de ex-internos, constatou-se a presença da religião institucionalizada, que atendia aos propósitos de vigilância e da terapêutica isolacionista. Os atuais portadores de hanseníase ainda sentem o peso do estigma da 'lepra' em determinadas situações. Foram aplicados também cinco questionários a profissionais de saúde do DHDS, que apresentam suas considerações sobre a religião do paciente e o tratamento. The article analyzes the religiosity of Hansen's disease patients who lived during two distinct treatment periods of the sick: that of internment in asylums and the current practice. Ten semi-structured interviews focused on health, religion and Hansen's disease, broaching the ways the two groups faced religion. In the former inmate group, the presence of institutionalized religion was noted, which served the purposes of vigilance and isolationist therapeutics. Present day Hansen's disease patients still feel the stigmatic weight of 'leprosy" in certain situations. Five questionnaires were also given to DHDS health professionals, who presented their considerations concerning the patient's religion and the treatment.